Comparative safety and efficacy of low dose ketamine and opioids for acute pain management at the emergency department - Asim, Syed Jehanzeb; Muhammad Aqil; Ali, Wajahat; Shehbaz, Lal; Nasir, Shua (International Journal of Endorsing Health Science Research, 2019)
Background: Pain is a complex phenomenon for which many pharmacological agents have been discovered and utilized for pain relief. Ketamine is a more preferred pain reliever over opioids in the emergency department (ED). The aim of this study was to compare the safety and efficacy of low dose ketamine (LDK) with morphine (opioid) for pain relief among patients presenting to the ED. Methodology: A prospective, cohort study was conducted over a sample of 280 patients presented with acute pain to the ED, Ziauddin University Hospital, Karachi. These patients were then divided into two groups via simple random sampling with randomization being assured using an online randomizer software tool. The 1st group (n=140) was given 0.2 mg/kg of LDK while 0.1 mg/kg of intravenous morphine (opioid) was given to the 2nd group (n=140). The pain intensity was measured using the Visual Analogue Scale (VAS) from admission to 60 mins, the records were taken after every 15 mins. The adverse events (AE’s) were also recorded for both groups. The data was then analyzed using SPSS Version 21 & Microsoft Excel 2016. Results: Out of 280 patients enrolled in the study, there was male majority i.e. 76.07% while the remaining were females with the mean age of 29±7 years. Within 15 minutes of initial dose administration in both groups, a marked reduction in pain intensity was observed. Reduced respiratory rate, pruritus and decreased O2 saturation were common AE’s observed, which were comparatively higher among patients receiving morphine as compared to ketamine. Conclusion: The efficacy of morphine (opium) and LDK is similar in alleviating pain in an emergency setting, however, LDK is visibly safer than its opioid counterpart and thus may be used as a safer alternative.